Poder, conflicto y orden. Penitenciaría Nacional Villa de las Palmas (Colombia) - Fajardo G., Miriam (Universidad Icesi, 2011)
In this paper, readers will find a description of such a particular social institutions as prison. The aim of this paper is to demonstrate how, along social interactions during daily life of detainees, relations between power and conflict have been constructed giving the way to the order alterative to the legal one endorsed by the State. Despite of the fact that this institution is based on the convergence of diverse actors of power like the administration, the guards, and the detainees, it is the relations between the latter two which are of a special interest to the author of this paper, since these actors are transformed into the key ones in terms of power needed to construct what we have called an alternative order.
Power, conflict and order. Villa de las Palmas (Colombia) National Penitentiary
Duzentos anos de ordem colonial marcaram na América Latina uma pauta de desenvolvimento institucional caracterizado pela tensão entre lei e cultura. De uma perspectiva histórica e neo-institucionalista, indica-se a distancia que existe entre os comportamentos tradicionais próprios do modo como se criou a ordem social e a ordem legal ¿imposta¿ por governantes que nem sempre corresponde de modo adequado à sociedade que pretende regular. O artigo analisa, a partir de onze romances hispano-americanos, as instituições formais e informais que emergem em três fases críticas do desenvolvimento institucional da América Latina.
Keywords: PRISIONES; PODER; CONFLICTO; INTERACCIÓN SOCIAL; PRISON; POWER; CONFLICT; SOCIAL INTERACTION; PRODUCCIÓN INTELECTUAL REGISTRADA - UNIVERSIDAD ICESI